2014
DOI: 10.1088/1674-1056/23/8/085202
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of nanoparticle coagulation in radio-frequency capacitively coupled C 2 H 2 discharges

Abstract: A self-consistent fluid model is employed to investigate the coagulation stage of nanoparticle formation, growth, charging, and transport in a radio-frequency capacitively coupled parallel-plate acetylene (C 2 H 2 ) discharge. In our simulation, the distribution of neutral species across the electrode gap is determined by mass continuity, momentum balance, and energy balance equations. Since a thermal gradient in the gas temperature induced by the flow of the neutral gas, a careful study of the thermophoretic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Moreover, since the gas flow is taken 075204-4 into account, a gas temperature gradient is presented in the discharge, which will make the gas molecules transfer more momentum from the hotter area of the plasma to the cooler area, and then a local maximum is created in front of the upper electrode. [21] However, in this work, we observe that by varying duty ratio, the peak of nanoparticle density gradually flow to the upper electrode. This is due to the fact that the negative ion density (H 2 CC − ) can diffuse to the wall in the pulseoff time, which is the main initial particle for the nanoparticle formation.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, since the gas flow is taken 075204-4 into account, a gas temperature gradient is presented in the discharge, which will make the gas molecules transfer more momentum from the hotter area of the plasma to the cooler area, and then a local maximum is created in front of the upper electrode. [21] However, in this work, we observe that by varying duty ratio, the peak of nanoparticle density gradually flow to the upper electrode. This is due to the fact that the negative ion density (H 2 CC − ) can diffuse to the wall in the pulseoff time, which is the main initial particle for the nanoparticle formation.…”
Section: Resultsmentioning
confidence: 54%
“…Previous work [21] has shown that gas flow has a great effect on the nanoparticle density spatial distribution. Hence, in Section 2, the neutral gas equations including the density, flux, and energy balances are taken into account and the mechanisms for particle formation are also elaborated.…”
Section: Introductionmentioning
confidence: 96%
“…For most cases, the only factors that vary very rapidly in the expression of S s-e are the rate constant that depends on T e and the electron density. The expression of the time-averaged value of S s-e over one RF period may be written: (10) Taking into account the discussion above, the expression of time-averaged continuity equations of long characteristic-time (LCT) species may be written as:…”
Section: Discharge Dynamic Modelmentioning
confidence: 99%
“…Capacitively coupled RF (CCRF) discharges in hydrocarbon (HC) containing mixtures have been the subject of interest for many decades [1], [2], [3]. These discharges were indeed used fairly early for the deposition of a variety of (multi-)functional carbon, i.e., Diamond-Like-carbon(DLC) [4] or TaC [5], and hydrogen-carbon coatings (aC:H) [6] with applications in a large number of fields such as tribology [7], diffusion barriers [8], anti-corrosion coatings [9], adhesion-enhancement [6], nanocomposites elaboration [10], biomedical [11], just to cite few examples. Although the carbon deposits elaborated by HC-containing discharges enable reaching a large number of functionalities, the physical properties and functional characteristics of the deposits are usually highly sensitive to the process characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [15] used a hybrid model to investigate the Ar/CF 4 gas ratio effects on the Si etch rate and profile uniformity in ICPs, revealing that the etching property is better at higher Ar/CF 4 gas ratios. Liu et al [16] used a fluid model to investigate influences of the gas flow rate, the radio frequency source voltage, and the pressure on the formation of dust particles in RF CCP acetylene (C 2 H 2 ) discharge, and they found that the gas flow rate is an important parameter for the particle growth mechanism. Moreover, some experimental research has also been done.…”
Section: Introductionmentioning
confidence: 99%